Erythema Multiforme after Pfizer- BioNTech COVID-19 Vaccination in Iraqi Patient (Medico Legal Update, 2021)
COVID-19 vaccine emerges as a revolutionary solution for the pandemic, but the rapid developmentof vaccines may misses non intentionally certain adverse events that may make a conflict on matter ofsafety of these vaccines.Skin reaction may be one of the most noted short term side effects of the vaccines and erythemamultiforme may be one of these presentations.